2015
DOI: 10.1016/j.socscimed.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of predictors of wellbeing among refugee youth eight years after resettlement in Melbourne, Australia

Abstract: This short report assesses the predictors of subjective health and happiness among a cohort of refugee youth over their first eight years in Australia. Five waves of data collection were conducted between 2004 (n = 120) and 2012-13 (n = 51) using mixed methods. Previous schooling, self-esteem, moving house in the previous year, a supportive social environment, stronger ethnic identity and perceived discrimination were significant predictors of wellbeing after adjusting for demographic and pre-migration factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
109
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 32 publications
4
109
0
1
Order By: Relevance
“…The participants who had experienced less security in housing since their arrival more frequently spoke of housing and safety as being closely interconnected. This finding is closely linked to that of Correa‐Velez et al (), who in a study of refugee youth 8 years into their resettlement process noted a significant negative impact on subjective experiences of wellbeing for those who had moved house in the prior year compared to those who had not. In the present study, visa type played an important role in perceived housing security, with participants holding permanent visas citing a higher sense of security in their housing than those on temporary visas.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The participants who had experienced less security in housing since their arrival more frequently spoke of housing and safety as being closely interconnected. This finding is closely linked to that of Correa‐Velez et al (), who in a study of refugee youth 8 years into their resettlement process noted a significant negative impact on subjective experiences of wellbeing for those who had moved house in the prior year compared to those who had not. In the present study, visa type played an important role in perceived housing security, with participants holding permanent visas citing a higher sense of security in their housing than those on temporary visas.…”
Section: Discussionsupporting
confidence: 71%
“…Given the variation in prevalence rates noted above, it is important to note that a number of risk and protective factors have been found to influence whether or not, and to what extent, children with refugee or asylum seeker backgrounds experience psychological distress or positive wellbeing outcomes following resettlement within countries such as Australia (Correa‐Velez, Gifford, & McMichael, ; Fazel et al, ; McFarlane, Kaplan, & Lawrence, ). Indeed, research has indicated that post‐settlement factors have a critical impact on child wellbeing, including through areas, such as education, social inclusion, and interaction with health services (Correa‐Velez et al, ; Due, Riggs, & Augoustinos, ).…”
Section: Background and Previous Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Overwhelming evidence shows that the meaner and more isolating the initial experience of reception, the poorer the physical and mental health of refugees, the weaker their sense of inclusion and wellbeing, and the lower their educational performance and chances of employment and economic productivity. [12][13][14][15][16][17][18] Systematic exclusion within resettlement communities can lead to alienation and exposure to radical influences. There is a clear moral case for the UK to do better.…”
mentioning
confidence: 99%